Fatores relacionados à disfunção e não função primária do enxerto no transplante de fígado - Coelho, Gustavo Rego (2007)
A hepatic insufficiency of the graft after liver transplantation can be defined with Primary Graft Dysfunction (PGD) or Primary Nonfunction (PNF). The Objective of this work is to evaluate the factors related to the donor and the recipient with PGD or PNF in patients submitted to the liver transplant. 176 patients were submitted a liver transplantation in the Walter Cantidio University Hospital of the Federal University of Ceara. The mortality, in 30 days, of the patients with normal enzymatic evolution was of 5%; of the patients with PGD was 19.7% and the patients with PNF was of 100%. The patients who had evolved in the postoperative (PO) with PGD and PNF had had 3,69 times more possibilities of death in 30 days than the patients who had had normal evolution. In this work, we evaluated donors and recipients vaiables: age, peak serum sodium, aminotransferases, liver steatosis, score MELD, the Cold Ischemia Time of Isquemia Fria (CIT) and the Warm Ischemia Time (WIT). The TIF bigger that 600 minutes, the WIT bigger that 55 minutes and liver steatosis > 30% were factors of risk for the PGD/PNF development. The correlation between the CIT, in minutes, with the evolution aminotransferases of the first one to the seventh postoperative day, it disclosed to significance statistic in 1st PO, 2nd PO, 3rd PO, 4th PO, 6th PO and 7th PO for AST. In relation the ALT had significance statistics in 1st PO, 2nd PO, 3rd PO, 4th PO, 5th PO, 6th PO and 7th PO. The correlation between WIT, in minutes, with the evolution of aminotransaminases the first one to the seventh postoperative day, revealed a significance statistic in 1st PO, 5th PO, 6th PO and 7th PO for AST. In relation the ALT we had significance statistic in the 1st PO. The liver steatosis > 30%, the increase of the CIT and the WIT consequently have correlation with increase of aminotransaminases in postoperative and the bigger risk of DPE/NFE.